A Novel Cuproptosis-Related Prognostic Model and the Hub Gene FDX1 Predict the Prognosis and Correlate with Immune Infiltration in Clear Cell Renal Cell Carcinoma. (10th December 2022) - Zhang, Kenan; Yang, Wuping; Zhang, Zedan; Ma, Kaifang; Li, Lei; Xu, Yawei; Qiu, Jianhui; Yu, Chaojian; Zhou, Jingcheng; Cai, Lin; Gong, Yanqing; Gong, Kan
Abstract : Clear cell renal cell carcinoma (ccRCC) is a common malignancy of the urological system with poor prognosis. Cuproptosis is a recently discovered novel manner of cell death, and the hub gene FDX1 could promote cuproptosis. However, the potential roles of cuproptosis-related genes (CRGs) and FDX1 for predicting prognosis, the immune microenvironment, and therapeutic response have been poorly studied in ccRCC. In the present study, The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) data were downloaded. CRGs were subjected to prognosis analysis, and three of them were used to construct the prognostic model by least absolute shrinkage and selection operator (LASSO) regression. The CRGs prognostic model showed excellent performance. Moreover, based on the risk score of the model, the nomogram was developed to predict 1-year, 3-year, and 5-year survival. Furthermore, the hub gene of cuproptosis, FDX1, was an independent prognostic biomarker in multivariate Cox regression analysis. The pan-cancer analysis showed that FDX1 was significantly downregulated and closely related to prognosis in ccRCC among 33 cancer types. Lower FDX1 was also correlated with worse clinicopathologic features. The lower expression of FDX1 in ccRCC was verified in the external database and our own database, which may be caused by DNA methylation. We further demonstrated that the tumor mutational burden (TMB) and immune cell infiltration were related to the expression of FDX1 . Immune response and drug sensitivity analysis revealed that immunotherapy or elesclomol may have a favorable treatment effect in the high FDX1 expression group and sunitinib or axitinib may work better in the low FDX1 expression group. In conclusion, we constructed a CRGs prognostic model and revealed that FDX1 could serve as a prognostic biomarker and predict therapeutic response in ccRCC. The study will provide a novel, precise, and individual treatment strategy for ccRCC patients.